Effect of tacticity-derived topological constraints in bactericidal peptides - Hazam, Prakash Kishore; Jerath, Gaurav; Kumar, Anil; Chaudhary, Nitin; Ramakrishnan, Vibin (Biochimica et biophysica acta. Biomembranes, 2017)
Topology is a key element in structure-activity relationship estimation while designing physiologically-active molecular constructs. Peptides may be a preferred choice for therapeutics, principally due to their biocompatibility, low toxicity and predictable metabolism. Peptide design only guarantees functional group constitution by opting specific amino acid sequence, and not their spatial orientation to bind and incite physiological response on chosen targets. This is principally because peptide conformation is subject to external flux, due to the isotactic stereochemistry of the peptide chain. Stereochemical engineering of the peptide main chain offers the possibility of multiplying the structural space of a typical sequence to many orders of magnitude, and limiting the otherwise fluxional non-specific functional group dispensation in space by offering greater conformational rigidity. We put to test, this conceptual possibility already established in theoretical models, by designing amphipathic peptide systems and experimenting with them on Gram-positive, Gram-negative and antibiotic-resistant bacteria. The unusual conformational rigidity and stability of syndiotactic peptides enable them to retain the designed electrostatic environment, while they encounter the membrane surface. All the six designed systems exhibited bactericidal activity, pointing to the utility and specificity of stereo-engineered peptide systems for therapeutic applications. Overall, we hope that this work provides important insights and useful directives in designing novel peptide systems with antimicrobial activity, by expanding the design space, incorporating D-amino acid as an additional design variable. [Display omitted] •Peptide based antimicrobials have low toxicity and predictable metabolism.•Stereo-chemical engineering of peptide sequences conserving amino-acid composition•Restricting spatial orientation of functional groups by conformational locking•Increasing the design space, with better specificity and differential activity•MIC value as low as 0.5μM against gram negative bacteria